Five tensions in climate adaptation research - Rickards, Lauren A.; Alexandra, Jason; Denham, Todd; Sanders, Anna (Frontiers in Climate, 2024)
Climate change adaptation is a maturing field of research imbued with many complexities and tensions. In this article, we outline five tensions that we observe in our own adaptation research. These are between: adaptation as a research topic and practical challenge; uncertainty in adaptation research and decision-makers' desire for certainty; the global scope of adaptation research and its highly context-specific nature; the newness of climate adaptation research and its push to address old problems; adaptation as a specialisation and the need for all researchers to engage. Our aim is to encourage critical discussion and reflection among researchers about how adaptation research is positioned within, shaped by and influences social and institutional settings. Given its emplaced character, adaptation research needs to attend to its content and context.